IDENTIFIKASI KESELAMATAN PENANGANAN LIMBAH PELUMAS PADA PT.ALTRAK 1978 BALIKPAPAN - Veza Azteria; Jamal Efendi (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
One of the B3 waste that needs to get special handling because it is produced in high amount in the society is the oil used oil (used oil). Used lubricating oil is produced from various human activities such as, industry, mining, and workshop. The purpose of this research is to know how to identify the handling safety of lubricant waste at PT.ALTRAK 1978 Balikpapan and to determine the proper controlling step. This research is designed as an observational descriptive evaluation research conducted by checklist, JSA (Job Safety Analysis) with observation, analyze , Observation and processing of data and information that has been collected systematically. The results showed that the handling of lubricant waste in PT.ALTRAK 1978 Balikpapan get the results of the value by using a percentage calculation of 72% if adjusted to the operational standard of the procedure is included in the assessment with enough results.Identifikasi safety handling lubricant waste in PT.ALTRAK 1978 Balikpapan can be done By making JSA (Job Safety Analysis) as well as adjustment to standard operational procedures with the implementation of the field.